2012
DOI: 10.1371/journal.pone.0037380
|View full text |Cite
|
Sign up to set email alerts
|

Validating the German Version of the Quality of Relationship Inventory: Confirming the Three-Factor Structure and Report of Psychometric Properties

Abstract: Research on psychosocial influences such as relationship characteristics has received increased attention in the clinical as well as social-psychological field. Several studies demonstrated that the quality of relationships, in particular with respect to the perceived support within intimate relationships, profoundly affects individuals' mental and physical health. There is, however, a limited choice of valid and internationally known assessments of relationship quality in Germany. We report the validation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
1
30
1
1
Order By: Relevance
“…It should also be noted that this study did not meet the results obtained in other studies carried out previously, that found a tri-factorial structure that matches the original version: in Portuguese context, studies of Neves (2006), Marques et al (2014) and Marques et al (2015); and internationally, studies from Verhofstadt et al (2006), Reiner et al (2012) and Cousson-Gélie et al (2013).…”
Section: Eissn: 2357-1330 Selection and Peer-review Under Responsibilitcontrasting
confidence: 94%
See 1 more Smart Citation
“…It should also be noted that this study did not meet the results obtained in other studies carried out previously, that found a tri-factorial structure that matches the original version: in Portuguese context, studies of Neves (2006), Marques et al (2014) and Marques et al (2015); and internationally, studies from Verhofstadt et al (2006), Reiner et al (2012) and Cousson-Gélie et al (2013).…”
Section: Eissn: 2357-1330 Selection and Peer-review Under Responsibilitcontrasting
confidence: 94%
“…Nakano et al (2002) found in a small sample of the Japanese population (40 couples), a factorial structure of 2 factors, where the depth and social support subscales were combined; Verhofstadt, Buysse, Rossel and Peene (2006) conducted a study with 286 Belgian couples and concluded that the original three-factor structure was the most suitable; Reiner, Beautel, Skaletz, Brahler and Stobel-Richter (2012), with a sample of 1494 adults, conducted the German validation of this scale, that also confirmed the tri-factorial structure of the QRI; Cousson-Gélie et al (2013) performed a confirmatory factor analysis, in France, with 388 cancer patients, which also corroborated the original factorial structure.…”
mentioning
confidence: 99%
“…Representative samples of the German population were recruited in 1999 (Sample 1, using the Partnership Questionnaire [PFB; Kliem, Kröger, Stöbel‐Richter, Hahlweg, & Brähler, 2012]), 2009 (Sample 2, using the German version of the Quality of Relationship Inventory [QRI]; Reiner, Beutel, Skaletz, Brähler, & Stöbel‐Richter, ), and 2010 (Sample 3, using the short form of the PFB [the PFB‐K; Kliem, Job, et al, 2012) with assistance from an independent agency that specializes in market, opinion, and social research (USUMA, Berlin, Germany; see http://www.usuma.com/). A three‐stage random sampling procedure was used to select (a) sample point regions from 258 regions that were determined on the basis of representative data, (b) target households within sample point regions using a random‐route procedure, and (a) target persons within target households according to a Kish selection grid.…”
Section: Methodsmentioning
confidence: 99%
“…The response rate in Sample 2 (see Reiner et al, , for details) of those contacted was approximately 61.9%. The sample consisted of 2,520 German adults.…”
Section: Methodsmentioning
confidence: 99%
“…It has proven useful in both clinical and nonclinical research on close relationships and has been validated in other languages (Reiner, Beutel, Skaletz, Brähler & Stöbel-Richter, 2012).…”
Section: Methodsmentioning
confidence: 99%